Scratch and community services: addressing quality education and reduced inequalities - Zainal Abidin, Nur Amirah Nabihah; Syed Ahmad, Tuan Sarifah Aini; Md Sallehuddin, Nur Hakimah; Hasan, Fatin Aliyah; Hasan, Nor Haniza (2025)
The integration of technology in education is important for students and teachers. One of the possibilities of integrating technology into education is by using Scratch. Since Scratch is a free web application, it can be accessed by anyone from anywhere and anytime. Moreover, it does not require users to learn any programming language as it applies a drag-and drop block system. It can also be used online and offline, offering 70 languages to choose from. With these features, Scratch can be introduced in community service programmes to address two Social Development Goals (SDG) namely SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities), in reducing the digital divide among teachers and students. It is important to promote the application of Scratch to teachers who cannot access expensive and advanced technology, empowering them to develop quality learning materials for students. Additionally, students can use Scratch for developing multimedia projects related to their subjects, making their learning fun and engaging. By using Scratch, various skills can be enhanced among teachers and students such as critical thinking, creative thinking, computer programming and computational thinking. However, underprivileged teachers and students may not have been exposed to Scratch. Thus, it is essential to introduce Scratch to them through community service programmes organised by certain organisations such as universities. This opens the possibility for teachers and students to learn Scratch, and experts from universities to share their expertise with the community.